STRATEGI BERSAING DIVISI BISNIS KARTU PADA PT BANK BNI SYARIAH - Azzubaidi, Salmah Hadi (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2016)
ABSTRACTThis study aims to analyze the opportunities and threats faced by the BSK Division of BNI Sharia, also possessed strengths and weaknesses BSK Division of BNI Sharia in developing the only Sharia-based credit card in Indonesia. Based on the result of the external environment analysis, it can be identified there are 11 opportunities factors and 6 threats factors for the BSK Division which can becompiled into EFE matrix, besides these factors affect the industry and the companys current strategies response to these factors. From the analysis of the internal environment above, it can be identified there are 6 strengths factors and 8 weaknesses factors of the BSK Division that can becompiled into IFE matrix, besides these factors affect the industry and the companys current strategies response to these factors. The analysis results of internal and external environment combined using matrix SFAS (Strategic factor analysis summary) to select the dominant factors that influence BSK Division significantly. Then analysis is needed to determine BSK Division market position by using BCG matrix, BSK Divisions competitive position against the credit card industry with Grand Strategy, and positioning the BSK Divisionâs portfolio business with IE matrix. Determining the strategy that will be implemented by using matrix QSPM is the further step. The strategies which has determined previously, will be formulated by comparing the external factors with internal factors using the SWOT matrix. In order to run this strategy, itâs necessary to shape it down into the functional level strategies by translating the chosen strategy to four perspectives: financial, customer, internal business process and learning growth using a balanced scorecard analysis tool, with results summarized in the map strategy. Â Acquiredbusiness strategies based on the analysis of external and internal to the BSK Division BNI Sharia arethe development strategy andmarket penetrationstrategy.Keywords: SWOT and Balanced Scorecard.